The Antiproliferative and Spermicide Effects of D-Limonene on Gonadal Function in Male Albino Rats: A Comprehensive Study on Spermatogenesis and Gonadal Morphometry - Akbar Dimas Herdiansyah; Neo Rakka Yudistira; Nadya Ashila Afandik; Nazwa Meiliza; Kresna Ryan Ardiansyah; Trilas Sardjito; Samira Musa Sasi (Media Kedokteran Hewan)
This study investigates the effects of D-Limonene on reproductive health parameters in albino rats, focusing on sperm quality and gonadal morphology. The study involved administering D-Limonene at various doses to assess their impacts on sperm parameters, including motility, viability, and abnormalities, as well as gonadal morphometry. The D-Limonene was applied at doses of 50, 100, and 150 mg/kg BW for 60 days, followed by histopathological analysis of testicular tissues. Results indicated that D-Limonene treatment revealed a dose-dependent decline in sperm quality parameters. Specifically, total motility, progressive motility, and viability decreased, while abnormality rates increased with higher D-Limonene doses. Notably, the highest dose (150 mg/kg BW) led to the most significant reductions in sperm motility and viability. Additionally, the presence of necrotic cells and structural changes in testicular tissues were observed, supporting the adverse impact of D-Limonene on reproductive function. The findings suggest that D-Limonene exhibits potential as an effective spermicide, highlighting its utility in population control applications. The study underscores the need for further research to fully understand the mechanisms behind these effects and their implications for reproductive health.